Stylometric Authorship Attribution for the Middle Dutch Mystical Tradition from Groenendaal. (2nd September 2018) - Kestemont, Mike
ABSTRACT: The well-known medieval Groenendaal monastery in Brabant has produced some of the finest examples of medieval Dutch literature, including Jan van Ruusbroec's œuvre, who together with Anne Frank, remains the most frequently translated Dutch author of all time. Authorship attribution nevertheless remains a serious scholarly concern when it comes to the corpus of mystical texts from Groenendaal: because of the general proximity of the Groenendaal authors, their œuvres can be difficult to delineate. In this paper, I apply a quantitative, style-based methodology for authorship attribution to a sizable corpus of Groenendaal authors. These computational techniques are borrowed from the innovative field of stylometry in the Digital Humanities. I will discuss how the experimental results obtained are able to confirm and complement many of the authorship-related hypotheses developed in traditional Middle Dutch studies. Additionally, this work aims to demonstrate the exciting scholarly potential of 'Distant Reading' for the study of the rich textual heritage from the medieval Low Countries.